Gait and gluteus medius alterations after Trochanteric-Entry intramedullary nailing: A retrospective quantitative analysis - Agar, Anil; Key, Sefa; Yildirim, Mustafa (Bmc, 2025)
Background: Trochanteric-entry intramedullary nailing (IMN) is widely used for the treatment of femoral shaft fractures. However, concerns remain regarding potential iatrogenic injury to the gluteus medius (GMed), a key hip abductor muscle essential for gait stability. Limited clinical studies have simultaneously investigated postoperative muscle morphology and gait biomechanics in this context. This retrospective study aimed to quantitatively evaluate gait and gluteus medius muscle alterations following trochanteric-entry intramedullary nailing in patients with healed femoral fractures. Methods: This retrospective observational study included 50 adult patients who underwent trochanteric-entry IMN between January 2020 and January 2024. At the 12th postoperative month, bilateral evaluations of GMed muscle thickness (ultrasonography), plantar pressure distribution, and spatiotemporal gait parameters (step length and cadence) were performed using the WIN-TRACK gait analysis system (Medicapteurs, France). Comparisons between operated and contralateral limbs were conducted with paired tests. Correlation, regression, and receiver operating characteristic (ROC) analyses were performed to examine associations between morphological and functional measures. Results: The operated limbs demonstrated significantly reduced step length (0.553 +/- 0.051 m vs. 0.584 +/- 0.045 m), cadence (104.6 +/- 11.2 vs. 109.9 +/- 10.8 steps/min), and GMed thickness (2.09 +/- 0.28 cm vs. 2.27 +/- 0.29 cm), all with p < 0.001. Plantar pressure variables, including maximum pressure, pressure-time integral, and contact area, were also significantly decreased on the operated side (p < 0.001). Effect size analyses revealed medium differences (Cohen's d: 0.48-0.63). Although step length showed weak positive correlations with GMed thickness and plantar loading parameters, regression (R-2 = 0.035, p = 0.643) and ROC analyses (AUC 0.46-0.53) indicated limited predictive accuracy. Conclusion: One year after trochanteric-entry IMN, patients exhibited persistent structural and functional asymmetries, including reduced step length, cadence, GMed thickness, and plantar pressure. Despite bone union and fracture healing, compensatory deficits remained evident. These findings highlight the need for postoperative rehabilitation protocols focusing on hip abductor strengthening, and gait re-education, as well as long-term monitoring of gluteus medius integrity.
Keywords: Femoral shaft fracture; Intramedullary nailing; Trochanteric entry; Gait analysis; Gluteus medius; Ultrasonography